Management of An-Nur Specialist Hospital and Lam Wah Ee Hospital : an evaluative study based on Maqasid al-Shari'ah - Asma' Amatullah binti Hasanuddin
Healthcare industry especially hospital plays a vital role in ensuring the well-being of the community. Many concept and certification programmes have been introduced into the industry including MSQH, ISO, JCI, ʻIbadah Friendly and few others to ensure the best quality in healthcare services. In 2014, a Shari'ah compliant certification programme MS1900:2014 was introduced. It is a quality assurance certification programme which underlined by Islamic teaching. Certified institution will be given a recognition as Shari'ah compliant. They must comply to the Islamic values and must incorporate Islamic jurisprudence in each of its business process where applicable. Currently An-Nur Specialist Hospital is the first private hospital certified as Shari'ah compliant. However, question rises on whether MS1900:2014 is comprehensive enough in defining the true beauty of Islam. Therefore, the purpose of this study is to define a comprehensive Sharīʻah Compliant concept according to the understanding of Maqasid al-Shari'ah by using a case study of two well-established hospitals with different models which are An-Nur Specialist Hospital and Lam Wah Ee Hospital. The case study uses in-depth, open-ended interview with the hospital's senior management representative. The interview was recorded, transcribed and evaluated based on thematic analysis to understand the practice. The outcome shows that the Shari'ah compliant concept has internally complied to Shari'ah jurisprudence and the non-Islamic institution are leading in giving values and goodness to the community. The combination of both concepts defines a comprehensive definition of Shari'ah compliant which is closer to the Maqasiid al-Shari'ah.